On the Effect of Lithium on the Energetics and Thermal Stability of Nano‐Sized Nonstoichiometric Magnesium Aluminate Spinel. Issue 8 (15th April 2016) - Mordekovitz, Yuval; Hayun, Shmuel
Abstract : The thermal stability of Li‐doped nonstoichiometric nano‐sized magnesium aluminate spinel, synthesized using a combustion synthesis method, was studied using XRD, FTIR, and high‐temperature differential scanning calorimetry. Li content within the magnesium aluminate spinel was determined to be a function of crystallite size and stoichiometry. For smaller crystallite sizes and higher Mg deficits, a greater amount of lithium could be incorporated into the structure as a solid solution between LiAl5 O8 and MgO· n Al2 O3 spinel, where n is the ratio between Al2 O3 and MgO. By assessing the intensities of the IR γ1, γ2, and γ5 modes, the degree of structural disorder (i.e., the inversion parameter and lithium occupancy) was defined. The results indicated that the as‐synthesized materials were heavily disordered. The surface enthalpy of the MgO·1.06Al2 O3, 1.51 ± 0.15 J/m 2, is in good agreement with the reported value for the same composition, 1.8 ± 0.3 J/m 2, measured using high‐temperature drop solution calorimetry. The surface enthalpies of MgO·1.21Al2 O3 and 0.20 at.% Li–MgO·1.21Al2 O3 were 1.17 ± 0.15 and 1.05 ± 0.12 J/m, respectively.